Excursion to Tindari - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2005)
Sicily's Inspector Salvo Montalbano investigates two seemingly unrelated crimes--the murder of a young Casanova and the mysterious disappearance of an elderly couple during an excursion to Tindari.